EFFECTS OF COLD ON BODY TEMPERATURE REGULATION OF WILD TURKEYS - Kurt J. Haroldson; Michael R. Riggs; Richard O. Kimmel (Wildlife Society Bulletin)
Abstract: In northern latitudes, many bird species conserve energy during cold periods by decreasing their resting phase body temperature (Tb). We evaluated the influence of cold stress on Tb regulation of wild turkeys (Meleagris gallopavo silvestris) during winter in Minnesota. Body temperatures were measured remotely with radiotelemetry from 11 captive wild turkeys during 10 trials. Turkeys were free ranging within large, outdoor pens while Tb was measured. Daily Tb patterns were characterized by a rapid decline during sunset, a shallow decline through the night, a rapid increase during sunrise, and a gradual increase during the day. During warm winter days (–8 to 11°C [18 to 52°F]), Tb cycled 2.0°C (3.6°F) from a mean daily minimum of 39.2°C (102.6°F) at night to a mean daily maximum of 41.2°C (106.2°F) during the day. With cold weather (–22 to –7°C [–8 to 19°F]), the daily minimum Tb remained higher (P = 0.020), increased at a lower rate during the sunrise period (P = 0.011), and then increased at a lesser rate during the remainder of the day (P = 0.049). We observed no evidence of controlled hypothermia at ambient temperatures (Ta) ≥ –22°C (–8°F). Wild turkeys cope with cold stress by increasing food consumption and selecting warm microclimates.